Design and fabrication of a simple cost effective spin coater for deposition of thin film - Ferdaus, Mohammad Meftahul; Rashid, Muhammad Mahbubur; Rahman, Mohammed Ataur (AENSI Publications, 2014)
This paper describes the design and fabrication of an economical spin coater for depositing thin films.Spin coater is a machine that can dispense a liquid onto a substrate uniformly. Some desirable properties of Spin coater such as ability to make defect free and uniform thin film, accuracy in rotation control together with a closed optimized process chamber etc. are maintained in this prototype spin coater.The materials used for making thin filmliquefied in a volatile solvent. Here the system is fabricated by using a dc motor and simple electronics circuit, in which the spinning speed can be controlled very easily. In this design the spinning speed is up to 3,000 rpm that can be controlled step by step manually. ZnO thin films are successfully prepared through this spin coater by sol-gel process. This thin film isa mixture of Zinc acetate dihydrate, ethanol anddi-ethanolamine. Thin filmdeposition by this cost effective spin coater is a very simple technique and can beused widelyfor preparing films of uniform thickness.